Novel method to generate high efficient devices which emit high quality light for illumination - (:unkn) unknown (Osram Opto Semiconductors GmbH, 2006)
What is disclosed is an electroluminescent apparatus comprising: an OLED device emitting light in the blue and green spectrums; and at least one down conversion layer, said down conversion layer absorbing at least part of the green spectrum light and emitting in at least one of the orange spectra and red spectra.
Keywords: 313/501.000; Film device; 313/504.000; Organic Light Emitting Diode; H05B 33/00 (20060101)